PRINSIP DASAR DAN RAGAM PENAFSIRAN KONTEKSTUAL DALAM KAJIAN TEKS AL-QUR’AN DAN HADIS NABI SAW - Muhammad Andi Rosa (Holistic al-Hadis, 2015)
Exegesis (tafsîr) is a dialogue between text and context. There are six kinds context in the exegesis of Qur’ânic verses and prophetic ḥadith: first of all, Socio-cultural context; the second, external context (i.e. revelation context; aspects relating to the emergence of a text), the interlocution context (siyâq al-takhâṭub) which is expressed in the language structure of the text; the third, internal structure of the verse (the structure of the text); the forth, linguistic context of the text; the fifth, the scientific context, i.e. context of modern sciences by paying attention to the ontology, epistemology, and axiology of the related topic; and sixth, the context of reading which aimed at deconstructing codes. There are three classifications of analysis in contextual exegesis: intrinsic analysis (mâ fî al-naṣṣ), extrinsic analysis (mâ ḥaula al-naṣṣ), and analysis to the exegesis of previous interpreters or relevant experts. In contextual exegesis, one has to do with some normative principles of exegesis (in mainstream), as mentioned by classical and contemporary interpreters.